2007
DOI: 10.1186/1471-2474-8-74
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high tibial osteotomy on the results of total knee arthroplasty: a matched case control study

Abstract: Background: We performed a matched case control study to assess the effect of prior high tibia valgus producing osteotomy on results and complications of total knee arthroplasty (TKA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 31 publications
5
56
2
5
Order By: Relevance
“…The 17 knees followed at an average of 59.4 months had outcomes of 94% with excellent or good results and no differences in knee score, function score, or ROM [4]. van Raaij et al [12] reported no differences between the knees in their patient-matched comparison with an average followup of 3.7 years. The final patient-matched studies also found HTOs do not have a negative effect on later TKAs [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 17 knees followed at an average of 59.4 months had outcomes of 94% with excellent or good results and no differences in knee score, function score, or ROM [4]. van Raaij et al [12] reported no differences between the knees in their patient-matched comparison with an average followup of 3.7 years. The final patient-matched studies also found HTOs do not have a negative effect on later TKAs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists regarding the success of a TKA after a prior HTO [2][3][4][6][7][8][9][10][11][12][13]. One might question whether failures would be greater in the long term as the HTO shortens the proximal tibia, the ligaments become lax and the proximal bone is more sclerotic.…”
Section: Introductionmentioning
confidence: 99%
“…The results seem to deteriorate in time and overall failure rates of 20% at five years and 40% at eight years are reported (8,9). Controversy exists regarding the success of a TKA after a previous HTO (7,8,10). Previous incisions, difficult exposure due to soft tissue scaring, patella baja, malunion or nonunion, offset of tibial shaft, change in the anatomy of tibial plateau, distortion of the joint line tilt and slope, retained osteosynthesis and subacute infections are technical challenges when performing a TKA after proximal tibia osteotomy (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, the natural history of following HTO is more or less expected and with longer follow-up, the results worsen. Therefore, a high tibial osteotomy can be considered as a way to postpone total knee arthroplasty (TKA) in young patients (5)(6)(7). The results seem to deteriorate in time and overall failure rates of 20% at five years and 40% at eight years are reported (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation